Towards Rheumatic Heart Disease vaccine development: Defining host immune responses to Group A Streptococcal infection in Cape Town - Salie, Mogamat (Department of Medicine, 2024)
Group A streptococcus (GAS) vaccines, as a primary prevention strategy, have the potential to prevent the spread of the bacteria, thus limiting post-sequelae diseases such as acute rheumatic fever (ARF) and rheumatic heart disease (RHD). Due to the limited supply of penicillin, adherence issues and problems associated with the diagnosis of post-sequelae diseases, a vaccine is thought to be the way forward on reducing the morbidity and mortality of ARF and RHD in low-resourced areas across the world. The latest vaccine formulation, a 30-valent M protein-based vaccine, currently in clinical trials is, however, challenged by the sheer volume of emm types (>230). This, along with the fact that significant emm types change over time, results in many gaps in protective efficacy. This body of work sought to contribute much-needed evidence in the quest for GAS vaccine development. This thesis provides a comprehensive understanding of the bacteria and its complexity regarding its emm type epidemiology and underlying immune effects within a population in Cape Town. This information could be used to make added improvements for the early detection and diagnosis of GAS infections, and further inform vaccine formulations, hopefully to ultimately reduce the burden of RHD in high-risk populations. The masters' thesis comprises four linked studies: a systematic review summarising the molecular epidemiology of GAS on the African continent, a longitudinal study, over a 2-year period of the molecular epidemiology of GAS, a systematic review assessing the association of GAS antigens with ARF and, an ELISA-based assessment of the human immune response to common GAS antigens. Chapter 1 provides the background and rationale for undertaking the study. Chapters 2, 3, 4, 5 report the respective studies described above. Finally, Chapter 6 serves to provide a context for the work with recommendations for further research and implications for clinical practice. Study I, published in mSphere 2020, highlights the dearth of epidemiological data found across the African content despite the high burden of GAS infections and post-sequalae diseases. Data, only available from five countries, indicated noticeable gaps in current vaccine formulations; for example, the StrepAnova vaccine, only affords 58.22% protective coverage. Study II serves to update an earlier study undertaken in Cape Town, South Africa, showing a continued significant prevalence of GAS in 256 children presenting with sore throat at community clinics. Among the 83 GAS strains isolated, characterisation through the emm typing procedure, documents a potential vaccine coverage of around 72%. Study III, published in Frontiers in Cardiovascular Medicine 2021, provides evidence confirming that a recent GAS infection is associated with increased levels of antibody titres to GAS antigens, SLO and DNase B in cases of ARF in comparison to controls. The study further indicates caution in the use of the upper limit of normal (ULN) when testing antibody responses and, rather, recommends the use of sequential sampling and testing sera against a panel of GAS antigens. Study IV provided evidence-based support for the utility of GAS-shared antigens and M peptides in documenting the characteristics of human immune responses following GAS infection. This study concludes that the array of GAS-specific antibody responses to GAS infection is broad, individuals demonstrate GAS-specific antibody responses in the absence of symptomatic GAS infection, GASnegative individuals exhibit pre-existing antibody levels and lastly, having a panel consisting of five shared GAS antigens, increased the overall sensitivity of predicting a preceding GAS infection to 73.7%. This thesis, emphasizes the need for population-based studies in Africa, endemic to GAS infection with a high burden of ARF/RHD. Secondly, this study provides empirical support for the value of sequential sampling in ascertaining recent infection, suggesting a panel of at least five antigens in diagnostic assessment. Finally, this work provides valuable epidemiological data and insights into GAS pathobiology, serving to aid in the development of effective, safe and affordable GAS vaccines for global deployment.